Gas diffusion layer for fuel cell, preparation method of gas diffusion layer and fuel cell

By adopting a gas diffusion layer structure composed of a base layer, a first microporous layer and a second microporous layer in the fuel cell, the synergistic effect of carbon material and hydrophobic binder is used to solve the problem of degradation in the performance of fuel cells under different humidification conditions, and stable operation and performance improvement are achieved.

CN119542436APending Publication Date: 2025-02-28CHINA AUTOMOTIVE INNOVATION CORP

Patent Information

Application Number
CN202311115984.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing fuel cell gas diffusion layer is difficult to adapt under different humidification conditions, resulting in a degradation of battery performance.

Method used

The gas diffusion layer structure is adopted, consisting of a base layer, a first microporous layer and a second microporous layer. The first microporous layer is composed of a carbon material and a first hydrophobic binder. The second microporous layer is composed of a hydrophilic modified carbon material and a second hydrophobic binder. The two act synergistically to adapt to different humidity enhancement conditions.

Benefits of technology

It achieves stable operation under different humidification conditions, avoids flooding problems, and improves the performance of fuel cells under low humidification conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542436A_ABST
    Figure CN119542436A_ABST
Patent Text Reader

Abstract

The invention provides a gas diffusion layer for a fuel cell, a preparation method of the gas diffusion layer and the fuel cell. The gas diffusion layer for the fuel cell comprises a substrate layer, a first microporous layer and a second microporous layer which are stacked in sequence, wherein the first microporous layer comprises a carbon material and a first hydrophobic binder; and the second microporous layer comprises a hydrophilic modified carbon material and a second hydrophobic binder. According to the gas diffusion layer structure provided by the invention, the microporous layer and the hydrophobic layer which have hydrophilic and hydrophobic effects at the same time have a synergistic effect, so that the gas diffusion layer structure can adapt to working conditions of different humidification conditions, the cell performance is maintained, and the performance of a fuel cell under low humidification can be improved without additional treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of fuel cells and relates to a gas diffusion layer for a fuel cell and a preparation method thereof and a fuel cell. Background Art

[0002] A fuel cell is a device that can convert the chemical energy in fuel into electrical energy. Among them, the proton exchange membrane fuel cell (PEMFC) has the advantages of fast start-up at room temperature, high power density, and low noise. It has high energy conversion efficiency and is not limited by the Carnot cycle. It has made significant progress in various fields, especially in the field of new energy vehicles, and has attracted the attention of a large number of researchers.

[0003] The core component of the fuel cell is the membrane electrode (MEA), which consists of a gas diffusion layer, a catalyst layer and a proton exchange membrane. Among them, the gas diffusion layer plays the role of supporting the catalyst layer, gas transmission and water management in the battery. The gas diffusion layer is composed of a porous substrate layer and a microporous layer. The substrate layer is generally carbon paper, carbon cloth or carbon felt, and the microporous layer is coated on one side after hydrophobic treatment. The microporous layer contains a conductive agent and a hydrophobic agent, which is in direct contact with the catalyst layer. Therefore, the microporous layer not only needs to be hydrophobic to remove water in time during the operation of the battery, but also needs to have a certain hydrophilicity to keep the inside of the battery moist under low humidification conditions to meet the requirements of the catalyst reaction.

[0004] CN114725398A provides a high-pressure resistant long-life gas diffusion layer and a preparation method and a fuel cell, wherein the high-pressure resistant long-life gas diffusion layer comprises a metal mesh, wherein a first hydrophobic layer and a second hydrophobic layer connected to each other are arranged in the metal mesh; the pore size of the first hydrophobic layer ranges from 1 μm to 50 μm, and the pore size of the second hydrophobic layer ranges from 10 nm to 500 nm. This document only considers the hydrophobic effect, and ignores the requirements of the battery under low humidification conditions.

[0005] CN112421052A discloses a gas diffusion layer for a proton exchange membrane fuel cell and its preparation method and application, wherein the microporous layer comprises conductive carbon black, a hydrophobic binder and polyacrylonitrile. The polyacrylonitrile / hydrophobic polymer binder composite microporous layer improves the performance of a single cell under low humidification conditions. However, the decomposition temperature of polyacrylonitrile is low, which affects the GDL sintering process and may cause uneven distribution of the hydrophobic agent.

[0006] Therefore, how to make the gas diffusion layer adapt to the cell operating conditions under different humidification conditions of the fuel cell and improve the performance of the fuel cell is a technical problem that needs to be solved urgently. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention aims to provide a gas diffusion layer for a fuel cell, a preparation method thereof, and a fuel cell. The gas diffusion layer structure provided by the present invention combines the microporous layer with both hydrophilic and hydrophobic effects with the hydrophobic layer to adapt to the working conditions of different humidification conditions, maintain the battery performance, and improve the performance of the fuel cell under low humidification without additional treatment.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a gas diffusion layer for a fuel cell, the gas diffusion layer for a fuel cell comprising a base layer, a first microporous layer, and a second microporous layer stacked in sequence;

[0010] Wherein, the first microporous layer comprises a carbon material and a first hydrophobic binder; and the second microporous layer comprises a hydrophilically modified carbon material and a second hydrophobic binder.

[0011] In the gas diffusion layer structure provided by the present invention, the carbon material that has not been hydrophilically modified in the inner layer (i.e., the structure closer to the substrate layer, the first microporous layer) can drain water in time under high moisture retention conditions to prevent the battery from being flooded, and at the same time cooperates with the hydrophilic and hydrophobic layer of the outer layer (the second microporous layer, the carbon material is hydrophilically treated). The carbon material has been hydrophilically modified, and the oxygen-containing groups on the surface have increased, making it more hydrophilic and able to retain water under low humidification conditions. At the same time, a hydrophobic agent is added to the inner layer so that it has both hydrophobic and hydrophilic pores, which can meet the requirement of timely drainage to prevent flooding when the humidity is high; thereby adapting to the working conditions of different humidification conditions, maintaining battery performance, and improving the performance of the fuel cell under low humidification without additional treatment.

[0012] In the present invention, the inner hydrophobic layer must cooperate with the outer hydrophilic and hydrophobic layer to jointly realize stable operation of the battery under different humidification conditions; if only the inner hydrophobic layer is contained, operation under low humidification conditions cannot be realized, and if only the outer hydrophilic and hydrophobic layer is contained, the battery will be flooded under high humidification conditions; and if the positions of the inner and outer layers are interchanged, the water management of the battery will be seriously affected; at the same time, if the outer layer is only a hydrophilic layer (that is, the second microporous layer does not have a hydrophobic function), the drainage problem under lower humidification conditions cannot be solved.

[0013] Preferably, the base layer comprises any one of carbon paper, carbon cloth or carbon felt, or a combination of at least two of them.

[0014] Preferably, a side of the base layer close to the first microporous layer is hydrophobically treated.

[0015] Preferably, the thickness of the first microporous layer is 10-30 μm, for example, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, 23 μm, 25 μm, 28 μm or 30 μm.

[0016] Preferably, the thickness of the second microporous layer is 10-20 μm, for example, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm or 20 μm.

[0017] In the present invention, if the thickness of the second microporous layer is too thin, it is not conducive to the drainage of the battery, and if it is too thick, the battery will be easily flooded.

[0018] Furthermore, the thickness of the first microporous layer and the thickness of the second microporous layer cooperate with each other to jointly realize the operation of the battery in a wider humidification window.

[0019] Preferably, the modifier in the hydrophilically modified carbon material comprises an acid or a base.

[0020] In the present invention, the carbon material is modified by acid or alkali to increase the oxygen-containing groups on its surface, making it more hydrophilic and able to retain water under low humidification conditions; if other modifiers are used, the modification results will be uncontrollable and the expected effect will not be achieved.

[0021] Preferably, the carbon material includes any one of conductive carbon black, carbon nanotubes or graphene, or a combination of at least two of them.

[0022] In the present invention, the specific type of conductive carbon black is not limited, and various materials that can be used as conductive carbon black are applicable to the present invention, including but not limited to acetylene black, Black Pearls 2000, Vulcan XC-72 or KB EC600JD, etc.

[0023] Preferably, the first hydrophobic binder and the second hydrophobic binder each independently include any one of polytetrafluoroethylene, polyvinylidene fluoride, perfluoroethylene propylene copolymer or polychlorotrifluoroethylene, or a combination of at least two thereof.

[0024] In a second aspect, the present invention provides a method for preparing a gas diffusion layer for a fuel cell as described in the first aspect, the preparation method comprising the following steps:

[0025] The carbon material, the first hydrophobic binder and the first dispersant are first mixed to obtain a first microporous layer slurry;

[0026] The hydrophilically modified carbon material, the second hydrophobic binder and the second dispersant are mixed for a second time to obtain a second microporous layer slurry;

[0027] The first microporous layer slurry is coated on the surface of the base layer to obtain the first microporous layer, and then the second microporous layer slurry is coated on the surface of the first microporous layer again, and heat-treated to obtain the gas diffusion layer for fuel cells.

[0028] The preparation method provided by the present invention prepares the microporous layer by a wet slurry method, the dispersion of each component is more uniform, the thickness of the microporous layer is also more uniform, and the preparation method is simple, and can adapt to different humidification conditions without adding additional additives or processing steps. The required materials are cheap and easy to obtain, and the source is wide, which can meet the needs of large-scale production.

[0029] Preferably, the hydrophilic modification method of the hydrophilic modified carbon material comprises:

[0030] The modifier solution is mixed with the carbon material for modification to obtain a hydrophilically modified carbon material.

[0031] Preferably, the modifier solution comprises an acid solution or an alkaline solution.

[0032] In the present invention, the acid solution includes but is not limited to nitric acid, phosphoric acid, sulfuric acid or sodium hypochlorite, and the alkaline solution includes but is not limited to sodium hydroxide or ammonia water.

[0033] Preferably, the modifier solution comprises at least two acid solutions or at least two alkaline solutions.

[0034] In the present invention, at least two acids or bases are selected as modifiers to enhance the acidity or alkalinity, thereby oxidizing the carbon material and achieving the purpose of hydrophilic modification.

[0035] Preferably, the mass concentration of the acid solution is ≥70%, for example, 70%, 71%, 72%, 73%, 74%, 75%, 76%, 77%, 78%, 79%, 80%, 85% or 90%, etc.

[0036] Preferably, the temperature of the mixing and modification is 50-80°C, for example, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C.

[0037] Preferably, the mixing and modification time is 0.5 to 3 h, for example, 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h.

[0038] Preferably, the base layer is first subjected to a hydrophobic treatment.

[0039] Preferably, in the first microporous layer slurry, the mass proportion of carbon material is 3-10%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0040] Preferably, in the first microporous layer slurry, the mass proportion of the first hydrophobic binder is 20-40%, for example, 20%, 25%, 30%, 35% or 40%.

[0041] Preferably, the first mixing comprises:

[0042] The carbon material is added to a first dispersant for first dispersion, and then a first hydrophobic binder is added to obtain a first microporous layer slurry.

[0043] Preferably, in the second microporous layer slurry, the mass proportion of the hydrophilically modified carbon material is 3-10%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%.

[0044] Preferably, in the second microporous layer slurry, the mass proportion of the second hydrophobic binder is 10-30%, for example, 10%, 15%, 20%, 25% or 30%.

[0045] Preferably, the second mixing comprises:

[0046] The hydrophilically modified carbon material is added to a second dispersant for second dispersion, and then a second hydrophobic binder is added to obtain a second microporous layer slurry.

[0047] Preferably, the first dispersant and the second dispersant each independently include any one of isopropanol, ethanol, water, acetone or ethylene glycol, or a combination of at least two thereof.

[0048] Preferably, both the first dispersion and the second dispersion include high-speed shear dispersion, and the rotation speed of the high-speed shear dispersion is 5000-8000 r / min, such as 5000 r / min, 6000 r / min, 7000 r / min or 8000 r / min.

[0049] In the present invention, the carbon material is dispersed in the dispersant by high-speed shear dispersion, so that the carbon powder can be better dispersed evenly, ensuring that the slurry is relatively fine and has no obvious particles.

[0050] Preferably, the coating method comprises knife coating.

[0051] Preferably, the speed of the scraping is 20-40 mm / s, for example, 20 mm / s, 25 mm / s, 30 mm / s, 35 mm / s or 40 mm / s.

[0052] Preferably, the temperature of the heat treatment is 300-360°C, for example, 300°C, 310°C, 320°C, 330°C, 340°C, 350°C or 360°C.

[0053] Preferably, the heat treatment time is 15 to 100 min, for example, 15 min, 20 min, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min or 100 min.

[0054] As a preferred technical solution, the preparation method comprises the following steps:

[0055] The preparation method comprises the following steps:

[0056] Adding the carbon material to the first dispersant and performing a first dispersion at a high-speed shearing speed of 5000 to 8000 r / min, and then adding the first hydrophobic binder to obtain a first microporous layer slurry;

[0057] The hydrophilically modified carbon material is added to a second dispersant and dispersed at a high-speed shear speed of 5000 to 8000 r / min, and then a second hydrophobic binder is added to obtain a second microporous layer slurry; wherein the hydrophilic modification method of the hydrophilically modified carbon material includes:

[0058] Mixing at least two acid solutions or at least two alkaline solutions with the carbon material for modification at 50 to 80° C. for 0.5 to 3 hours to obtain a hydrophilically modified carbon material;

[0059] The first microporous layer slurry is scraped onto the surface of the base layer at a speed of 20 to 40 mm / s to obtain the first microporous layer, and then the second microporous layer slurry is scraped onto the surface of the first microporous layer again at a speed of 20 to 40 mm / s, and heat treated at 300 to 360°C for 15 to 100 minutes to obtain a gas diffusion layer for a fuel cell.

[0060] In a third aspect, the present invention provides a fuel cell, comprising the gas diffusion layer as described in the first aspect.

[0061] Compared with the prior art, the present invention has the following beneficial effects:

[0062] In the gas diffusion layer structure provided by the present invention, the carbon material that has not been hydrophilically modified in the inner layer (i.e., the structure closer to the substrate layer, the first microporous layer) can drain water in time under high moisture retention conditions to prevent the battery from being flooded; at the same time, it cooperates with the hydrophobic layer of the outer layer (the second microporous layer, the carbon material is hydrophilically treated), the carbon material has been hydrophilically modified, the oxygen-containing groups on the surface increase, and it is more hydrophilic and can retain water under low humidification conditions, and at the same time, a hydrophobic agent is added to the inner layer so that it has both hydrophobic and hydrophilic pores, which can meet the requirement of timely drainage when the humidity is high to prevent flooding; thereby adapting to the working conditions of different humidification conditions, maintaining battery performance, and improving the performance of the fuel cell under low humidification without additional treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 The polarization curve of the battery assembled based on the gas diffusion layer of Example 1.

[0064] Figure 2 This is the polarization curve of the battery assembled based on the gas diffusion layer of Comparative Example 1.

[0065] Figure 3 This is the polarization curve of the battery assembled based on the gas diffusion layer of Comparative Example 2. DETAILED DESCRIPTION

[0066] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0067] Example 1

[0068] This embodiment provides a gas diffusion layer for a fuel cell, the gas diffusion layer for a fuel cell comprising a base layer, a first microporous layer (thickness of 30 μm) and a second microporous layer (thickness of 15 μm) stacked in sequence;

[0069] Wherein, the second microporous layer comprises hydrophilically modified XC-72 carbon black and polytetrafluoroethylene (PTFE); the first microporous layer comprises XC-72 carbon black and polytetrafluoroethylene (PTFE).

[0070] The preparation method of the gas diffusion layer is as follows:

[0071] (1) Take an appropriate amount of XC-72 carbon black, add it to a mixed solution of concentrated nitric acid and concentrated sulfuric acid, wherein the volume ratio of concentrated nitric acid to concentrated sulfuric acid is 1:3, and then stir at 60°C for 3 hours. After the reaction is completed, cool to room temperature, and use deionized water for suction filtration and washing; after washing, place it in a vacuum oven for drying to obtain hydrophilically modified carbon black (XC-72-O);

[0072] (2) Weigh 100g of isopropanol solution in a beaker, weigh XC-72 (unmodified), add it to the solution in batches under high-speed shearing of an emulsifier, and then disperse it at 6000r / min for 120min. Switch to mechanical stirring, weigh 60wt% of PTFE emulsion (first hydrophobic binder), add it dropwise to the stirred slurry, and continue stirring for 1h using mechanical stirring to obtain MPL slurry 1 (first microporous layer slurry, wherein the mass proportion of XC-72 in the slurry is 5%, and the mass proportion of PTFE emulsion in the slurry is 15%);

[0073] Weigh 100g of isopropanol solution in a beaker, weigh XC-72-O, add it to the solution in batches under high-speed shear of an emulsifier, and then disperse it at 6000r / min for 120min; remove the slurry from the emulsifier and continue stirring it with mechanical stirring, weigh 60wt% of PTFE emulsion (the first hydrophobic binder), add it dropwise to the stirred slurry, and continue stirring it for 1h with mechanical stirring to obtain MPL slurry 2 (the second microporous layer slurry, wherein the mass proportion of XC-72-O in the slurry is 5%, and the mass proportion of PTFE emulsion in the slurry is 15%);

[0074] (3) The first microporous layer slurry is evenly scraped on one side of the carbon paper treated with PTFE hydrophobic treatment at a scraping speed of 30 mm / s, and then placed in an oven at 60°C for drying (to obtain the first microporous layer), and then taken out, and the second microporous layer slurry is evenly scraped on the outer side of the dried first microporous layer at a scraping speed of 30 mm / s, and placed in an oven at 60°C for drying; the dried gas diffusion layer is placed in a muffle furnace for heat treatment at 360°C for 30 min, with a heating rate of 5°C / min, to obtain the gas diffusion layer.

[0075] Example 2

[0076] This embodiment provides a gas diffusion layer for a fuel cell, the gas diffusion layer for a fuel cell comprising a base layer, a first microporous layer (thickness of 10 μm) and a second microporous layer (thickness of 10 μm) stacked in sequence;

[0077] Wherein, the second microporous layer comprises hydrophilically modified XC-72 carbon black and polytetrafluoroethylene (PTFE); the first microporous layer comprises XC-72 carbon black and polytetrafluoroethylene (PTFE).

[0078] The preparation method of the gas diffusion layer is as follows:

[0079] (1) Take an appropriate amount of XC-72 carbon black, add it to a mixed solution of concentrated nitric acid and concentrated sulfuric acid, wherein the volume ratio of concentrated nitric acid to concentrated sulfuric acid is 1:3, and then stir at 80°C for 1 hour. After the reaction is completed, cool to room temperature, and use deionized water for suction filtration and washing; after washing, place it in a vacuum oven for drying to obtain hydrophilically modified carbon black (XC-72-O);

[0080] (2) Weigh 100g of isopropanol solution in a beaker, weigh XC-72 (unmodified), add it to the solution in batches under high-speed shearing of an emulsifier, and then disperse it at 6000r / min for 120min. Switch to mechanical stirring, weigh 60wt% of PTFE emulsion (first hydrophobic binder), add it dropwise to the stirred slurry, and continue stirring for 1h using mechanical stirring to obtain MPL slurry 1 (first microporous layer slurry, wherein the mass proportion of XC-72 in the slurry is 5%, and the mass proportion of PTFE emulsion in the slurry is 15%);

[0081] Weigh 100g of isopropanol solution in a beaker, weigh XC-72-O, add it to the solution in batches under high-speed shear of an emulsifier, and then disperse it at 6000r / min for 120min; remove the slurry from the emulsifier and continue stirring it with mechanical stirring, weigh 60wt% of PTFE emulsion (the first hydrophobic binder), add it dropwise to the stirred slurry, and continue stirring it for 1h with mechanical stirring to obtain MPL slurry 2 (the second microporous layer slurry, wherein the mass proportion of XC-72-O in the slurry is 3%, and the mass proportion of PTFE emulsion in the slurry is 10%);

[0082] (3) The first microporous layer slurry is evenly scraped on one side of the carbon paper treated with PTFE hydrophobic treatment at a scraping speed of 20 mm / s, and then placed in an oven at 60°C for drying (to obtain the first microporous layer), and then taken out, and the second microporous layer slurry is evenly scraped on the outer side of the dried first microporous layer at a scraping speed of 20 mm / s, and placed in an oven at 60°C for drying; the dried gas diffusion layer is placed in a muffle furnace for heat treatment at 300°C for 80 min, with a heating rate of 5°C / min, to obtain the gas diffusion layer.

[0083] Example 3

[0084] This embodiment provides a gas diffusion layer for a fuel cell, the gas diffusion layer for a fuel cell comprising a base layer, a first microporous layer (thickness of 20 μm) and a second microporous layer (thickness of 20 μm) stacked in sequence;

[0085] Wherein, the second microporous layer comprises hydrophilically modified acetylene black and perfluoroethylene propylene copolymer (FEP); the first microporous layer comprises acetylene black and perfluoroethylene propylene copolymer (FEP).

[0086] The preparation method of the gas diffusion layer is as follows:

[0087] (1) taking an appropriate amount of acetylene black, adding it to a mixed solution of concentrated nitric acid and concentrated sulfuric acid, wherein the ratio of concentrated nitric acid to concentrated sulfuric acid is 1:3, and then stirring at 50° C. for 3 hours. After the reaction is completed, cooling to room temperature, filtering and washing with deionized water; after washing, placing in a vacuum oven to dry, obtaining hydrophilically modified acetylene black (acetylene black-O);

[0088] (2) Weigh 100g of isopropanol solution in a beaker, weigh XC-72 (unmodified), add it to the solution in batches under high-speed shearing of an emulsifier, and then disperse it at 6000r / min for 120min. Switch to mechanical stirring, weigh 60wt% of PTFE emulsion (first hydrophobic binder), add it dropwise to the stirred slurry, and continue stirring for 1h using mechanical stirring to obtain MPL slurry 1 (first microporous layer slurry, wherein the mass proportion of XC-72 in the slurry is 5%, and the mass proportion of PTFE emulsion in the slurry is 15%);

[0089] Weigh 100g of isopropanol solution in a beaker, weigh XC-72-O, add it to the solution in batches under high-speed shear of an emulsifier, and then disperse it at 6000r / min for 120min; remove the slurry from the emulsifier and continue stirring it with mechanical stirring, weigh 60wt% of PTFE emulsion (the first hydrophobic binder), add it dropwise to the stirred slurry, and continue stirring it for 1h with mechanical stirring to obtain MPL slurry 2 (the second microporous layer slurry, wherein the mass proportion of XC-72-O in the slurry is 10%, and the mass proportion of PTFE emulsion in the slurry is 30%);

[0090] (3) The first microporous layer slurry is evenly scraped on one side of the carbon paper treated with PTFE hydrophobic treatment at a scraping speed of 30 mm / s, and then placed in an oven at 60°C for drying (to obtain the first microporous layer), and then taken out, and the second microporous layer slurry is evenly scraped on the outer side of the dried first microporous layer at a scraping speed of 30 mm / s, and placed in an oven at 60°C for drying; the dried gas diffusion layer is placed in a muffle furnace for heat treatment at 330°C for 50 min, with a heating rate of 5°C / min, to obtain the gas diffusion layer.

[0091] Example 4

[0092] The difference between this embodiment and embodiment 1 is that the thickness of the second microporous layer in this embodiment is 5 μm.

[0093] The rest of the preparation methods and parameters were the same as those in Example 1.

[0094] Example 5

[0095] The difference between this embodiment and embodiment 1 is that the thickness of the second microporous layer in this embodiment is 25 μm.

[0096] The rest of the preparation methods and parameters were the same as those in Example 1.

[0097] Comparative Example 1

[0098] This comparative example provides a gas diffusion layer for a fuel cell. The difference between this comparative example and Example 1 is that this comparative example does not contain a second microporous layer but only contains a first microporous layer.

[0099] In the preparation method, the modification process in step (1) and the preparation of the first microporous layer slurry in step (2) are not performed.

[0100] The rest of the preparation methods and parameters were the same as those in Example 1.

[0101] Comparative Example 2

[0102] The difference between this comparative example and Example 1 is that this comparative example does not contain the first microporous layer but only contains the second microporous layer.

[0103] In the preparation method, the second microporous layer slurry is prepared in step (2).

[0104] The rest of the preparation methods and parameters were the same as those in Example 1.

[0105] Comparative Example 3

[0106] The difference between this comparative example and the preliminary example 1 is that the positions of the first microporous layer and the second microporous layer are interchanged in this comparative example.

[0107] The preparation method was adjusted adaptively.

[0108] The rest of the preparation methods and parameters were the same as those in Example 1.

[0109] Figure 1 The polarization curve of the battery assembled based on the gas diffusion layer of Example 1 shows that the performance is good under low humidification conditions and there is no obvious water flooding under high current density.

[0110] Figure 2 The polarization curve of the battery assembled based on the gas diffusion layer of Comparative Example 1 is shown. The lack of the second microporous layer with hydrophilic and hydrophobic synergy leads to slightly poor performance under low humidification.

[0111] Figure 3 The polarization curve of the battery assembled based on the gas diffusion layer of comparative example 2 is shown, and there is obvious water flooding under high current density, indicating that if there is only a second microporous layer with hydrophilic and hydrophobic coordination in the gas diffusion layer, but no first microporous layer, drainage will be difficult.

[0112] from Figure 1-Figure 3It can be seen that only when the microporous layer has both moisturizing and hydrophobic effects, that is, the first microporous layer and the second microporous layer must cooperate and exist at the same time, can the needs of the battery under different humidification conditions be met.

[0113] The gas diffusion layers provided in Examples 1-5 and Comparative Examples 1-3 were assembled into a single cell, the cell end plates, gas diffusion layers and membrane electrodes were stacked in order, the cells were assembled, the polarization curves were tested, and the power density was tested under uniform 50% RH conditions at the cathode and anode. The specific test results are shown in Table 1.

[0114] Table 1

[0115] <![CDATA[Power density (mW / cm 2 @ 2 A / cm 2 )]]> Example 1 1114.0 Example 2 1098.3 Example 3 1086.5 Example 4 1076.2 Example 5 1069.4 Comparative Example 1 1016.2 Comparative Example 2 947.9 Comparative Example 3 876.7

[0116] From the data results of Examples 1, 4 and 5, it can be seen that in the present invention, if the thickness of the second microporous layer is too thin, it is not conducive to the drainage of the battery, and if it is too thick, the battery will be easily flooded. That is, the present invention achieves better performance of the battery under different humidification conditions through the coordinated cooperation of the thickness of the first microporous layer and the thickness of the second microporous layer.

[0117] From the data results of Example 1 and Comparative Examples 1-3, it can be seen that the present invention must achieve the purpose of stable operation under a wide humidification window through the coordinated cooperation of the first microporous layer and the second microporous layer, and the stacking order is fixed.

[0118] To sum up, the gas diffusion layer structure prepared by wet pulping in the present invention, the carbon material in the inner layer (i.e., the structure closer to the base layer, the first microporous layer) that has not been hydrophilically modified can drain water in time under high moisture retention conditions to prevent the battery from being flooded, and at the same time cooperate with the hydrophobic layer of the outer layer (the second microporous layer, the carbon material is hydrophilically treated). The carbon material has been hydrophilically modified, and the oxygen-containing groups on the surface have increased, making it more hydrophilic and able to retain water under low humidification conditions. At the same time, a hydrophobic agent is added to the inner layer so that it has both hydrophobic and hydrophilic pores, which can meet the requirements of timely drainage and prevention of flooding when the humidity is high; thereby adapting to the working conditions of different humidification conditions, maintaining battery performance, and improving the performance of the fuel cell under low humidification without additional treatment.

[0119] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A gas diffusion layer for a fuel cell, characterized in that: The gas diffusion layer for a fuel cell comprises a base layer, a first microporous layer and a second microporous layer stacked in sequence; Wherein, the first microporous layer comprises a carbon material and a first hydrophobic binder; and the second microporous layer comprises a hydrophilically modified carbon material and a second hydrophobic binder.

2. The gas diffusion layer for a fuel cell according to claim 1, characterized in that: The base layer comprises any one of carbon paper, carbon cloth or carbon felt or a combination of at least two thereof; Preferably, a side of the base layer close to the first microporous layer is hydrophobically treated.

3. The gas diffusion layer for a fuel cell according to claim 1 or 2, characterized in that: The thickness of the first microporous layer is 10 to 30 μm; Preferably, the second microporous layer has a thickness of 10-20 μm.

4. The gas diffusion layer for a fuel cell according to any one of claims 1 to 3, characterized in that: The modifier in the hydrophilically modified carbon material includes an acid or a base; Preferably, the carbon material includes any one of conductive carbon black, carbon nanotubes or graphene, or a combination of at least two thereof; Preferably, the first hydrophobic binder and the second hydrophobic binder each independently include any one of polytetrafluoroethylene, polyvinylidene fluoride, perfluoroethylene propylene copolymer or polychlorotrifluoroethylene, or a combination of at least two thereof.

5. A method for preparing a gas diffusion layer for a fuel cell according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: The carbon material, the first hydrophobic binder and the first dispersant are first mixed to obtain a first microporous layer slurry; The hydrophilically modified carbon material, the second hydrophobic binder and the second dispersant are mixed for a second time to obtain a second microporous layer slurry; The first microporous layer slurry is coated on the surface of the base layer to obtain the first microporous layer, and then the second microporous layer slurry is coated on the surface of the first microporous layer again, and heat-treated to obtain the gas diffusion layer for the fuel cell.

6. The method for preparing a gas diffusion layer for a fuel cell according to claim 5, characterized in that: The hydrophilic modification method of the hydrophilic modified carbon material comprises: Mixing the modifier solution with the carbon material for modification to obtain a hydrophilically modified carbon material; Preferably, the modifier solution comprises an acid solution or an alkaline solution; Preferably, the modifier solution includes at least two acid solutions or at least two alkaline solutions; Preferably, the mass concentration of the acid solution is ≥70%; Preferably, the temperature of the mixing and modification is 50 to 80°C; Preferably, the mixing and modification time is 0.5 to 3 hours; Preferably, the base layer is first subjected to a hydrophobic treatment.

7. The method for preparing a gas diffusion layer for a fuel cell according to claim 5 or 6, characterized in that: In the first microporous layer slurry, the mass proportion of carbon material is 3-10%; Preferably, in the first microporous layer slurry, the mass proportion of the first hydrophobic binder is 20-40%; Preferably, the first mixing comprises: Adding the carbon material into a first dispersant for first dispersion, and then adding a first hydrophobic binder to obtain a first microporous layer slurry; Preferably, in the second microporous layer slurry, the mass proportion of the hydrophilically modified carbon material is 3-10%; Preferably, in the second microporous layer slurry, the mass proportion of the second hydrophobic binder is 10-30%; Preferably, the second mixing comprises: Adding the hydrophilically modified carbon material into a second dispersant for second dispersion, and then adding a second hydrophobic binder to obtain a second microporous layer slurry; Preferably, the first dispersant and the second dispersant each independently include any one or a combination of at least two of isopropanol, ethanol, water, acetone or ethylene glycol; Preferably, the first dispersion and the second dispersion both include high-speed shear dispersion, and the rotation speed of the high-speed shear dispersion is 5000-8000 r / min.

8. The method for preparing a gas diffusion layer for a fuel cell according to any one of claims 5 to 7, characterized in that: The coating method includes scraping; Preferably, the speed of the scraping is 20 to 40 mm / s; Preferably, the temperature of the heat treatment is 300-360°C; Preferably, the heat treatment time is 15 to 100 minutes.

9. The method for preparing a gas diffusion layer for a fuel cell according to any one of claims 5 to 8, characterized in that: The preparation method comprises the following steps: Adding the carbon material to the first dispersant and performing a first dispersion at a high-speed shearing speed of 5000 to 8000 r / min, and then adding the first hydrophobic binder to obtain a first microporous layer slurry; The hydrophilically modified carbon material is added to a second dispersant and dispersed at a high-speed shear speed of 5000 to 8000 r / min, and then a second hydrophobic binder is added to obtain a second microporous layer slurry; Among them, the hydrophilic modification method of the hydrophilic modified carbon material includes: Mixing at least two acid solutions or at least two alkaline solutions with the carbon material for modification at 50 to 80° C. for 0.5 to 3 hours to obtain a hydrophilically modified carbon material; The first microporous layer slurry is scraped onto the surface of the base layer at a speed of 20 to 40 mm / s to obtain the first microporous layer, and then the second microporous layer slurry is scraped onto the surface of the first microporous layer again at a speed of 20 to 40 mm / s, and heat treated at 300 to 360°C for 15 to 100 minutes to obtain a gas diffusion layer for a fuel cell.

10. A fuel cell, characterized in that: The fuel cell comprises the gas diffusion layer according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Gas diffusion layer for proton exchange film fuel cell and preparation method and application thereof

    CN112421052A

Cited By

  • Double-layer microporous layer for fuel cell, preparation method of double-layer microporous layer, gas diffusion layer and fuel cell

    CN121583941A